2020
DOI: 10.1109/tmech.2019.2959379
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Framework for the Synthesis of Powered Floor Systems

Abstract: One of the most pressing issues in the field of mobile robotics is that of power delivery. By being fundamentally unattached to the environment, these systems often employ batteries. However, this can have some limitations related to cost, battery life etc.; a promising approach is that of powered floors, where a specially designed contact array is connected to the robot, and slides on a surface in which conducting bands are laid out, providing a continuous and uninterrupted electrical connection. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…In a previous paper [1], we focused on a systematic study of the alternating bands sliding-contact based powered floor introduced by C. Shannon in the 1950s [27]; we provided a comprehensive framework for contact patterns for robots, based on regular polygons of n sides. In particular we demonstrated that triangle-and rectangle-shaped patterns cannot always guarantee contact, and that Shannon's pattern itself has several limitations.…”
Section: Requires External Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper [1], we focused on a systematic study of the alternating bands sliding-contact based powered floor introduced by C. Shannon in the 1950s [27]; we provided a comprehensive framework for contact patterns for robots, based on regular polygons of n sides. In particular we demonstrated that triangle-and rectangle-shaped patterns cannot always guarantee contact, and that Shannon's pattern itself has several limitations.…”
Section: Requires External Sensorsmentioning
confidence: 99%
“…Delivering electrical power to mobile robots or, more generally, to mobile systems is a challenge in many operative fields: transportation, automation, and logistics. Power supply systems based on sliding contacts [1] are an effective solution to power a large number of mobile robots, especially in swarm robotics applications, where powering a single robot by manually recharging the battery is time-consuming. They are also simple to implement and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, фактор присутствия в среде, охлаждающей инструмент, частиц эрозии, в том числе из-за адгезии к электроду, ведет к некоторому изменению динамики процесса эрозии с временной вариацией формы электрода и к нарушению качества результата воздействия эрозии на материал [1,4,8,25,26]. В зоне эрозии действует несколько факторов, влияющих на вариации формы электрода [5].…”
Section: Introductionunclassified
“…Перекрытие частицами эрозии малоразмерного канала их движения, это фактор сильного изменения эрозии, массопереноса, _____________________________________________________________________________________  Деева В.С., Слободян С.М., Электронная обработка материалов, 2022, 58(2), 12-20. термодинамики и т.п. [21,23,24,27] [15,23,24], биомедицинских средств и систем [16,26], в технике и средствах конструирования наноэлектронных элементов на кристалле [31], в технике устройств микро-насосов и средств электроосмоса [6,26,[32][33][34], а так же во многих других отраслях техники, включая технику управления передачей тепла в микроэлектромеханических устройствах и микроэлектронных системах [35]. Представленные в [35], результаты учитывают использование влияния на движение микропотока среды действия силы Лоренца.…”
Section: Introductionunclassified
See 1 more Smart Citation